2022
DOI: 10.3389/fncel.2022.977205
|View full text |Cite
|
Sign up to set email alerts
|

Aminoacyl transfer ribonucleic acid synthetase complex-interacting multifunctional protein 1 induces microglial activation and M1 polarization via the mitogen-activated protein kinase/nuclear factor-kappa B signaling pathway

Abstract: Activation of microglia, which is the primary immune cell of the central nervous system, plays an important role in neuroinflammation associated with several neuronal diseases. Aminoacyl tRNA synthetase (ARS) complex-interacting multifunctional protein 1 (AIMP1), a structural component of the multienzyme ARS complex, is secreted to trigger a pro-inflammatory function and has been associated with several inflammatory diseases. However, the effect of AIMP1 on microglial activation remains unknown. AIMP1 elevated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…This suggests that proteins contained within microglia-derived EVs could play a role in mRNA processing as well as protein synthesis in the recipient cell. Furthermore, Oh et al 2022 reported that Aminoacyl tRNA synthetase (ARS) complex-interacting multifunctional protein 1 (AIMP1), a structural component of the multienzyme ARS complex, can induce microglial activation and has been associated with several inflammatory diseases 37 . Based on this, microglia specific-EV signatures could be related to protein-synthesis machinery and influence activation of recipient cells.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that proteins contained within microglia-derived EVs could play a role in mRNA processing as well as protein synthesis in the recipient cell. Furthermore, Oh et al 2022 reported that Aminoacyl tRNA synthetase (ARS) complex-interacting multifunctional protein 1 (AIMP1), a structural component of the multienzyme ARS complex, can induce microglial activation and has been associated with several inflammatory diseases 37 . Based on this, microglia specific-EV signatures could be related to protein-synthesis machinery and influence activation of recipient cells.…”
Section: Discussionmentioning
confidence: 99%